Christina Gerhardt. Screening the Red Army Faction: Historical and Cultural Memory. Bloomsbury Academic, 2018; Christina Gerhardt, Marco Abel, ed. Celluloid Revolt: German Screen Cultures and the Long 1968. Camden House, 2019. - Svea Braeunert (Studies in 20th & 21st Century Literature, 2020)
Review of Christina Gerhardt. Screening the Red Army Faction: Historical and Cultural Memory. Bloomsbury Academic, 2018, xii + 307 pp. and Christina Gerhardt, Marco Abel, ed. Celluloid Revolt: German Screen Cultures and the Long 1968. Camden House, 2019, 330 pp.
Keywords: terrorism; film; 1968; Red Army Faction